Morbidity and mortality in a prospective cohort of people who were homeless during the COVID-19 pandemic - Loubiere, Sandrine; Hafrad, Ikrame; Monfardini, Elisabetta; Mosnier, Marine; Bosetti, Thomas; Auquier, Pascal; Mosnier, Emilie; Tinland, Aurélie (Frontiers in Public Health, 2023)
Introduction: Certain living conditions, such as homelessness, increase health risks in epidemic situations. We conducted a prospective observational cohort study to investigates the impact of the COVID-19 pandemic on morbidity and mortality in homeless adult people who were homelesss. Methods: The study population comprised around 5040% of the entire homeless population experiencing homelessness in Marseille. They were enrolled at 48 different locations during the first pandemic wave (June to August 2020) and were followed up 3 and 6 months later. Rapid serological screening for SARS-CoV-2 was performed by community outreach teams at each follow-up, who also conducted interviews. Death registers and hospital administrative databases were consulted. Results: A total of 1332 participants (mean age 40.1 years [SD 14.2], women 339 (29.9%)) were enrolled in the cohort. Of these, 192 (14.4%) participants were found positive for COVID-19 and were propensity score matched (1:3) and compared with 553 non-COVID-19 cases. Living in emergency shelters was associated with COVID-19 infection. While 56.3% of the COVID-19-infected cohort reported no symptoms, 25.0% were hospitalised due to the severity of the disease. Presence of three or more pre-existing comorbidities was associated with allcause hospitalisation. Among COVID-19 cases, only older age was associated with COVID-19 hospitalisation. Three deaths occurred in the cohort, two of which were among the COVID-19 cases.The study provides new evidence that the homeless population experiencing homelessness faces higher risks of infection and hospitalisation due to COVID-19 than the general population: in Marseille, 3.6% of people of the same age were infected and 3.4% hospitalized. Despite the efforts of public authorities, the health inequities experienced by homeless people who are homeless remained major. More intensive and appropriate integrated care and earlier re-housing are needed.